Effects of sugars and amino-oxyacetic acid on the longevity of pollinated Dendrobium Pompadour flowers - Razali, Zuliana; Yip, Y.K.; Nair, H.; Boyce, Amru Nasrulhaq; Somasundram, Chandran (Horticultural Society of India, 2010)
Experiments were carried out to investigate the effects of different types and concentration of sugars and aminooxyacetic acid (AOA) and their combination in extending the vase-life of pollinated Dendrobium Pompadour flowers. The results obtained showed that the most effective treatments in extending the vase-life of pollinated Dendrobium Pompadour flowers and delaying the post-pollination symptoms were 0.05 mM AOA and the treatment which combined 0.05 mM AOA with 4 glucose. Both treatments showed a vase-life of up to 13 days, about 6 folds more than that of the control. Furthermore positive effects were also observed in a delay of weight loss, improved water uptake, change in petal thickness and colour. A combination of 0.05 mM AOA and 2 sucrose extended the vase-life of flowers up to 5 days. Inclusion of 4 glucose and 2 sucrose alone only prolonged the vase-life of flowers two days more compared to that of the control. Holding solutions containing sugars alone only prolonged the vase-life of flowers for just two days more compared to control. As has been studied in other experiments, pH of the holding solutions containing sugars alone maintained values of 5.0-7.0 while those with AOA and a combination of AOA and sugar at 3.0-5.0. Aminooxyacetic acid (AOA) and its combination with glucose extended the vase-life of pollinated Dendrobium Pompadour and also delayed the post-pollination symptoms.